Hubungan Adaptabilitas Karier Terhadap Prestasi Akademik - Liska Mayora Febriani; M. Amin Sihabuddin; Hartika Utami Fitri (Journal of Society Counseling, 2023)
This research examines about. "The relationship between student career adaptability to academic achievement of the Islamic counseling guidance study program, the Faculty of Indictment and Communication at UIN Raden Fatah Palembang". This study aims to find out first, a description of the career adaptability of students in the Islamic counseling guidance study program and second, to find out whether there is a relationship between student career adaptability and academic achievement of the Islamic counseling study program, the faculty of dakwa and communication, Uin Raden Fatah Palembang. The study used a quantitative correlation approach with a population of 141 respondents and a sample of 56 respondents. Sampling used simple random sampling. Data collection techniques using questionnaires and documentation. The data analysis technique was through the Pearson product moment test with the help of Windows SPSS Version 22. The results of the study showed first, that the career adaptability description of students was at a moderate level of 77% 109 people. and secondly, it is known that the result of Asymp sig.(2-tailed) is 0.00. Value 0.000 <0.05, it can be concluded that Ha is accepted and H0 is rejected, which means that there is a relationship between student career adaptability to academic achievement with a relationship value of 0.676 in a strong relationship and has a positive direction.